Study on Lightweight of Gearbox Shell for a Heavy Commercial Vehicle - Hu Li; Tang Senquan; Yang Qiliang; Wang Bo (Jixie chuandong)
In order to achieve a heavy commercial vehicle gearbox lightweight，the gray cast iron shell is replaced by aluminum alloy shell.Firstly，the finite element model is verified by modal test.Then the dynamic loads of the five bearings of the shell are obtained by the method of multi-body dynamics，and the strain energy of the shell is obtained based on the static analysis.Then，the mathematical model of four influencing factors on the mass of plate and shell is established to determine the order of the influence of each influencing factor on the mass of plate and shell.The results show that the strength and stiffness of the lightweight shell meet the requirements.